Phase I study of single‐dose pharmacokinetics and pharmacodynamics of belatacept in adolescent kidney transplant recipients. Issue 4 (22nd January 2019) - Moudgil, Asha; Dharnidharka, Vikas R.; Feig, Daniel I.; Warshaw, Barry L.; Perera, Vidya; Murthy, Bindu; Roberts, Mustimbo E.; Polinsky, Martin S.; Ettenger, Robert B.
Abstract : Belatacept is an intravenously infused selective T cell costimulation blocker approved for preventing organ rejection in renal transplant recipients aged ≥18 years. This phase I trial examined the pharmacokinetics and pharmacodynamics (percentage CD86 receptor occupancy [%CD86RO]) of a single dose of belatacept (7.5 mg/kg) administered to kidney transplant recipients aged 12‐17 years receiving a stable calcineurin inhibitor–based immunosuppressive regimen. Nine adolescents (mean age 15.1 years) who were seropositive for Epstein‐Barr virus were enrolled; all completed the 6‐month study. Pharmacokinetics suggested relatively low variability of exposure (coefficients of variation for maximum observed serum concentration [ C max ] and area under the serum concentration‐time curve from time zero extrapolated to infinity [AUC0‐ INF ] were 20% and 25%, respectively). Mean half‐life ( T 1/2 ) occurred 7.2 days postinfusion. Belatacept total body clearance was 0.48 mL/h/kg, and volume of distribution at steady‐state ( V ss ) was low at 0.09 L/kg. Compared with historical data from healthy adult volunteers administered a single dose of belatacept 10 mg/kg and adult kidney transplant recipients administered multiple doses of belatacept 5 mg/kg, pharmacokinetic values for adolescents were similar, indicating consistency across adolescent and adult populations. Mean %CD86RO increased with increasing belatacept concentration, indicating a direct relationship between pharmacokinetics and pharmacodynamics. Four patients reported 7 serious adverse events; none was considered related to belatacept. These data will inform belatacept dose selection in future studies of adolescent kidney transplant recipients. Abstract : Results from a phase I study of adolescent renal transplant recipients administered a single intravenous infusion of belatacept at 7.5 mg/kg show comparable pharmacokinetic and pharmacodynamic values to those obtained historically from healthy adult volunteers given a single dose of belatacept (10 mg/kg) and adult kidney transplant recipients administered multiple doses of belatacept (5mg/kg/dose).